PENELITIAN PALEOMAGNETIK DAN GAYA BERAT KAITANNYA DENGAN PEMBENTUKAN FORMASI BATUAN DI SULAWESI SELATAN SERTA HUBUNGANNYA DENGAN SELAT MAKASAR DAN KALIMANTAN - Saultan Panjaitan (Jurnal Geologi dan Sumberdaya Mineral, 2009)
Rocks formed in South Sulawesi consist of: 1. Ultramaphic rocks of Triassic age having the polarity D= 268°, I= -45°, rotation anticlockwise 92°, and paleolatitude position -26.50°S. 2. The melange complexes of Cretaceous age having the polarity D= 330°, I= - 30°, rotation anticlockwise 30° and paleo lattitude position - 16.10°S. 3. Tonasa Formation of Middle Miocene-Early Eocene age having polarity D= 280°, I= -28°, rotation anticlockwise 80° and paleo latitude position -14.80°S. 4. Camba Formation of Middle-Late Miocene age having the polarity D= 279°, I= -24°, rotation anticlockwise 81° and paleo latitude position - 12.5°S 5. Limestones of Tacipi Member from Walanae Formation of Middle Miocene age, having polarity D= 280°, I= -9° rotation anticlockwise 80°, and paleo latitude position -4.5°S. 6. Sandstone of Walanae Formation of Pleistocene age and upper layer having the polarity D= 358°, I= -7°, very small rotation anticlockwise between 0° – 2° S and paleo latitude position -3.5°S. Gravity analysis , Paleomagnetism and GPS analysis indicate that rotation occured in South Sulawesi since Trias until now is anticlockwise. There for rifting concept in Makasar Strait at Recent diagram is less acceptable. Kalimantan and Sulawesi possible had ever closed as indicated from the movement of Kalimantan to the south since Late Trias at -17°S. At the same age Sulawesi moved northward to latitude -16.10°S. Then both islands were amalgamed and moved together northward with anticlockwise rotation between 50° to 92°. During the Trias age Kalimantan was derived from Asian Continent,while rock group in South Sulawesi at the same age were derived from south latitude and then moved together, by Australian continent movement. Keywords: rifting, paleomagnetic, anticlockwise, latitude, rotation, sea floor, strait.